Experimental Research on the Room Air Conditioner with Thermoelectric Subcooler - Jin Tingxiang; L (Zhileng xuebao)
In the vapor compression refrigeration system, the increasing subcooling degree of air conditioner can improve the refrigerating capacity and the coefficient of performance (COP). Based on the principle of thermoelectric refrigeration to increase the subcooling degree, the air conditioner with thermoelectric subcooler was designed in this paper. The performance of air conditioner was tested and compared before and after equipped with the subcooler in the following three operation conditions: the minimum cooling operation condition, the rated cooling operation condition and the maximum cooling operation condition. The results show that, the exit subcooling degrees of condenser at three operation conditions are improved by 2.3 ℃, 1.9 ℃ and 1.5 ℃, respectively. The refrigeration capacities of the air conditioner are increased 3.6%, 3.2% and 4%, respectively. Meanwhile, the COPs of the air conditioner are increased 3.7%, 3.1% and 4%, respectively. In the future, the performance of air conditioner can be improved by the optimization of operation conditions of thermoelectric element.